Strength as concrete with spent bleaching earth as cement replacement - Lina Chong Ann, Yi (2010)
This study is to investigate the compressive and flexural strength of concrete with partial replacement of 30% and 40% spent bleaching earth (SBE). The field of studies also covers important parameters in determining the drying shrinkage and the element of curing condition. A total of 54 cubes (150 x 150 x 150 mm) and 54prisms (100 x 100 x 500 mm) were prepared in three groups according to different binder content and the samples were cured under two curing conditions which were air and water curing for 7, 14 and 28 days before testing. Three types of mixtures were prepared based on the level of replacement of 30% SBE concrete, 40% SBE concrete and 100% OPC as the control mixture. The mix ratio is 1:0.6:2.1:3.1(cement:water:sand:aggregate). The result showed that the 30% spent bleaching earth mixtures achieved higher compressive and flexural strength than 40% spent bleaching earth mixture for both curing condition. For air curing, 30% SBE concrete mixture achieved 8.6MPa of compressive strength and 2.44MPa of flexural strength. For water curing, 30% SBE concrete mixture achieved 9.89MPa of compressive strength and 2.76MPa of flexural strength On the other hand, 40% SBE concrete mixture achieved 8.43MPa of compressive strength and 2.58MPa of flexural strength under air curing. For water curing, 40% SBE concrete achieved 9.61MPa of compressive strength and 2.73MPa of flexural strength. The 30% spent bleaching earth mixture shows highest drying shrinkage strain compared to other mixture in both curing condition. Through the observation, the spent bleaching earth showed lower early strength gain but a satisfying improvement of strength as the time increased. This study offered that the SBE as the new material implementation of lightweight composite design and construction utilizes existing technologies which lead to another choice in the current markets for greener environment.